Newly-onset type 1 diabetes mellitus precipitated by COVID-19 in an 8-month-old infant - Soliman, Ashraf T; Al-Amri , Mohamed; Alleethy, Khaled; Alaaraj, Nada; Hamed, Noor; De Sanctis, Vincenzo (Acta Biomedica Atenei Parmensis, 2020)
Summary. Type 1 diabetes mellitus (T1DM) is rare in infants and toddlers and is usually associated with a relatively high mortality when complicated with diabetic ketoacidosis (DKA). In infants, the classical symptoms of DKA are atypical and therefore many infants with DKA are mistreated for infections. We report a case of DKA precipitated by COVID-19 in an 8-month-old infant with newly diagnosed diabetes mellitus. This case is reported in view of its rarity and originality. The relation between T1DM and COVID19 infection is discussed.